Squamous Metaplasia in Colonic Tubulovillous Adenoma: A Three Case Series and review of literature. (28th October 2021) - Duhoki, D; Allison, D; Wiley, E
Abstract: Introduction/Objective: Although squamous metaplasia of colonic tubulovillous adenoma is a rare phenomenon, colorectal polyps can show focal squamous metaplasia. While the exact cause in unknown, it has been suggested that mechanical irritation, torsion and chronic inflammation may predispose to squamous metaplasia within large colonic polyps. Methods/Case Report: We observed this finding in two men and one woman with colorectal polyps who underwent endoscopic mucosal resection in a three-week timeframe. In two cases the polyps were rectal, while in the third case, it was located in the descending colon. Polyp size ranged from 1-5 cm and were semi-pedunculated. Histologically, all three lesions were tubulovillous adenomas with focal high-grade dysplasia and multiple foci of squamous metaplasia characterized by cells with benign-appearing nuclei, eosinophilic cytoplasm, and solid growth pattern. Some metaplastic foci approached the muscularis mucosae, mimicking adenocarcinoma at low power magnification. Interestingly, these metaplastic foci were reactive against p16 immunohistochemical stain. Results (if a Case Study enter NA): NA Conclusion: We present these three cases to add to the few previously reported. Pathologists should be aware of this finding to avoid the overdiagnosis of invasive carcinoma in the setting of nested and pseudo invasive squamous morules, especially in polyps with high grade dysplasia. In addition, squamous metaplasia could be a precursor lesion for colorectal squamous cell carcinoma.